Analysis of the Impact of TikTok on Elementary School Students' Politeness - Sitanggang, Raysyah Putri (Lembaga Riset Mutiara Akbar, 2025)
The use of the TikTok application has become a very popular phenomenon among teenagers and young people, affecting various aspects of their lives, including social behavior and politeness. TikTok, as a video sharing platform, not only provides entertainment, but also functions as a means of communication that affects the way users interact and behave in everyday life. Based on the results of interviews and observations, it was found that boys claimed that TikTok did not affect their politeness, but observations showed that they often said bad words, made noise in class, and imitated expressions and gestures from TikTok. In contrast, female students admitted that TikTok affected their lives, for example by using bad words when angry. Several students, such as SA, AN, and RA, had imitated the behavior they saw on TikTok, including swearing when provoked. They also showed indifference to calls from parents or older siblings when they were busy watching TikTok content. This study also showed differences in attitudes towards trends on TikTok, where male students did not feel pressured to follow trends, while female students felt excluded if they did not have a TikTok account. The results of this study revealed that the use of TikTok has different impacts on the behavior of male and female students. Although TikTok can be a means of having fun and reducing stress, its impact on politeness and social interaction shows the importance of developing soft skills in children in facing the challenges of this digital era.